Customized crossover in evolutionary sets of safe ship trajectories - Szłapczyński, Rafał; Szłapczyńska, Joanna (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents selected aspects of evolutionary sets of safe ship trajectories?a method which applies evolutionary algorithms and some of the assumptions of game theory to solving ship encounter situations. For given positions and motion parameters of the ships, the method finds a near optimal set of safe trajectories of all ships involved in an encounter.
Keywords: evolutionary algorithms; ship collision avoidance; decision support systems